Effect of feeding frequency on performance of growing pigs - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The influence of frequency of feeding on weight gain, feed efficiency, and carcass measurements was investigated, using 48 pigs averaging 40 pounds. Differences in daily gain among pigs fed ad libitum, twice a day or once a day were not significant. However, pigs fed only once/48 hours gained significantly (P<.05) slower than pigs on the other treatments. Pigs allowed access to feed once/24 hrs. or once/48 hrs. were more efficient (P<.05) in feed utilization than pigs fed twice/ 24 hrs. or those fed ad libitum. Carcass measurements did not differ significantly among pigs fed ad libitum, twice/ 24 hrs., or once/24 hrs. Pigs allowed access to feed only once/48 hrs. had significantly (P<.05) less backfat and smaller loin eye areas than pigs fed more frequently.
Swine Industry Day 1971 is known as Swine Day, 1971
Keywords: Swine; Performance; Growing pigs; Libitum